Prevalence of and Factors Affecting Acquisition of Intestinal Cryptosporidiosis in Malaysian Children with Malignancies at Oncology Ward, Institute of Paediatrics, Hospital Kuala Lumpur, Malaysia - Elbeshti, Lubna Mohamed (2011)
Cryptosporidium parvum is an opportunistic parasitic agent that has a world-wide distribution. The disease caused by this parasite can be severe and very difficult to manage in immunocompromised patients especially in children with malignancies. However, data on immunocompromised children in Malaysia is very much lacking. The aim of this study was to estimate the prevalence of cryptosporidiosis in children with different types of malignancies and to study factors that might contribute to acquisition of cryptosporidiosis. A cross-sectional study was conducted over 10 months from November 2009 until August 2010 in Institute of Pediatrics, Hospital Kuala Lumpur. A self-administered questionnaire was used and medical records were obtained. Stool samples were examined for the Cryptosporidium oocyst by using two different techniques i.e. modified Ziehl-Neelsen stain and Immunochromatographic (ICT) assays (RIDA-Quick Cryptosporidium R-Biopharm, Germany). One hundred and ten stool samples were collected from children (56 boys, 49 girls) with different types of malignancies between the ages of 3 months and 17 years (mean age: 2 years). The majority of those children were the Malays (75.2%), followed by the Chinese (11.4%), Indians (8.6%) and others (4.8%) The most common type of lympho-hematopoietic malignancies was acute lymphoblastic leukemia (38.1%), followed by acute myeloid leukemia (8.6%), suspected leukemia (8.6%), lymphoma (7.6%), and chronic myeloid leukemia (1.9%). Whereas, among non-lympho-hematopoietic malignancies, brain tumor represented 11.4% of cases, followed by retinoblastoma (5.7%), hepatoblastoma (3.8%), Wilm‟s tumor (2.9%), pleuropulmonary blastoma (1.9%) and right adrenal cortical tumor (0.9%). Fever was presented in (83.8%) of those patients, followed by diarrhea (54.3%). All stool samples were negative for Cryptosporidium oocysts by two different techniques. (33.3%) from those patients had history of admission to other wards, (29.5%) had history of animal contact, (24.8%) had history of swimming in the swimming pool. In terms of precautionary measures practiced, (80.9%) and (75.2%) washed their hands before and after eating, or after going to the toilet respectively. In addition, preventive measures that were also observed: (16.2%) had history of admission to day-care center, (2.9%) had history of drinking tap water, and (0.9%) had history of travel. In this present study, we documented a zero prevalence rate of cryptosporidiosis amongst children with malignancies despite higher prevalence rates being reported in other developing countries. Our results may suggest that the children with malignancies are at low risk of acquiring cryptosporidiosis because of good personal hygiene, good infection control and practices in the hospital, and improve water supply system. Screening for Cryptosporidium oocysts may not be necessary in those patients. Our findings suggest that routine screening of stools for Cryptosporidium might not be necessary for our patients. However, we believe large multicenter studies throughout Malaysia are needed to establish the true prevalence and characteristics of cryptosporidiosis among children with malignancies.